Gender disparity in health-related quality of life and fatigue after living renal donation - Sommerer, Claudia; Estelmann, Sarah Anna Gertrud; Metzendorf, Nicole; Leuschner, Maren; Zeier, Martin (BMC nephrology, 2018)
Background: The clinical outcome and health-related quality of life (HRQoL) of living kidney donors is mostly not detrimental, but some donors experience impairment after donation. Gender-specific effects of living kidney donors was evaluated. Methods: Clinical outcome was assessed in living kidney donors and HRQoL was obtained by self-reporting validated test systems as the Multidimensional Fatigue Inventory (MFI-20), the Short Form 36 (SF-36), and the Patient Health Questionnaire (PHQ-9). Results: Two hundred and eleven (211) living renal donors were evaluated (female 62.2%). Response rate was 80.8%. In both genders, a decrease of renal function of 26% was observed after donation. De novo antihypertensives were introduced in 28.3% of women and 36.5% of men. HRQoL was comparable in female and male donors, except for mental HRQoL, which was lower in 51- to 60-year-old female donors, compared to age-matched male donors and to the female general population. Female donors aged 40-59 years demonstrated more fatigue than the age-matched general population. A low mental HRQoL (MCS; SF-36) was associated with higher values for fatigue (General Fatigue Score; MFI-20) in both genders. Multiple regression analysis detected the General Fatigue score of the MFI-20 questionnaire and depression identified by the PHQ-9 score as independent variables predicting MCS of the SF-36 in both genders. Lower age at time of donation contributed to a lower MCS in female donors. Conclusions: Overall, HRQoL in living kidney donors exceeds that of the general population. Inferior mental health status and fatigue seem to be a problem, especially in middle-aged female donors, but not in all female donors. Psychological evaluation pre donation and psychological support post donation are required. - Electronic supplementary material - The online version of this article (10.1186/s12882-018-1187-8) contains supplementary material, which is available to authorized users.